Puolikorkean pensasmustikan taimituotanto ja viljelykokeet Savossa vuosina 1986-1992 = Studies on the propagation and cultivation of half-high blueberries in Finland /Savo district) in 1986 to 1992 - Paasisalo, Sirpa (Kuopio University publications, 1993)
Abstract.